Finite element analysis for thermal enhancement in power law hybrid nanofluid - Nazir, Umar; Sohail, Muhammad; Singh, Abha; Muhsen, Sami; Galal, Ahmed M.; Tag El Din, El Sayed M.; Hussain, Syed M. (Frontiers in Physics, 2022)
Ethylene glycol with nanoparticles behaves as a non-Newtonian fluid and its rheology can be best predicted by the power-law rheological approach. Further nanoparticles (silicon dioxide and aluminum oxide) are responsible for anti-oxidation, anti-evaporation, and anti-aging. Therefore, their dispersion in ethylene glycol is considered as these properties make the nanofluid stable. This article examines the impact of (silicon dioxide and aluminum oxide) on the thermal enhancement of ethylene glycol as it is a worldwide used coolant. Moreover, simultaneous effects of temperature and concentration gradients, Joule heating, viscous dissipation, thermal radiations, and Bouncy forces are modeled and developed investigations are computed by FEM. An increase in temperature due to composition gradient and an increase in concentration due to temperature gradient are observed. A significant increase in the Ohmic phenomenon with an increase in the intensity of the magnetic field is observed. Numerical experiments are performed by considering single-type nanoparticles and hybrid-type nanoparticles. During the visualization of simulations, it is observed that the effective thermal conductivity of hybrid nanoparticles.